Knowledge encapsulation for focused search from pervasive devices. - Aridor, Yariv (ACM transactions on information systems.)
Mobile knowledge seekers often need access to information on the Web during a meeting or on the road, while away from their desktop. A common practice today is to use pervasive devices such as Personal Digital Assistants or mobile phones. However, these devices have inherent constraints (e.g., slow communication, form factor) which often make information discovery tasks impractical.In this paper, we present a new focused-search approach specifically oriented for the mode of work and the constraints dictated by pervasive devices. It combines focused search within specific topics with encapsulation of topic-specific information in a persistent repository. One key characteristic of these persistent repositories is that their footprint is small enough to fit on local devices, and yet they are rich enough to support many information discovery tasks in disconnected mode. More specifically, we suggest a representation for topic-specific information based on "knowledge-agent bases" that comprise all the information necessary to access information about a topic (under the form of key concepts and key Web pages) and assist in the full search process from query formulation assistance to result scanning on the device itself. The key contribution of our work is the coupling of focused search with encapsulated knowledge representation making information discovery from pervasive devices practical as well as efficient. We describe our model in detail and demonstrate its aspects through sample scenarios.